MOTIVASI BIDAN DALAM PENGGUNAAN PARTOGRAF PADA IBU BERSALIN DI IBI RANTING WELERI KABUPATEN KENDAL - Sri Rahayu (Midwifery Care Journal, 2020)
The use of partographs is active and open behavior which is a response to a stimulusin the form of real or open action. Partograph is a tool for early detection of problemsand complications in childbirth such as prolonged labor, bleeding and fetal distress,so that you can immediately take action or refer the mother in optimal conditions. Theresearch objective was to determine the motivation of the midwives in usingpartograph in IBI Weleri Branch, Kendal Regency.This research is an observationalstudy with a cross-sectional approach. The research instrument used a structuredquestionnaire and observation sheets. The number of samples was 81 respondents,using simple random sampling technique with proportional allocation. The resultsshowed that most of the respondents had a Diploma III education (53.3%), with anaverage working period of 1-10 years, and an average age 30 years. Most of therespondents have good motivation such as responsibility, recognition, and the jobitself. There is a relationship between responsibility, recognition, work itself and themotivation of the midwife in using partographs. The variable that becomes the basisfor the motivation of midwives in using partographs is responsibility. The Health Officeneeds to increase the sense of responsibility of the midwife through the explanationand understanding of the partograph as the main task of the midwife, the importanceof the partograph, providing awards, and periodic evaluation. In addition, midwivesare given the opportunity to take part in training, especially APN.